Synthesis and Electrochemical Properties of BaFe1−xCuxO3−δ Perovskite Oxide for IT‐SOFC Cathode. Issue 6 (9th November 2016) - Xie, D.; Guo, W.; Guo, R.; Liu, Z.; Sun, D.; Meng, L.; Zheng, M.; Wang, B.
Abstract: A series of iron‐based perovskite oxides BaFe1− x Cu x O3− δ ( x = 0.10, 0.15, 0.20 and 0.25, abbreviated as BFC‐10, BFC‐15, BFC‐20 and BFC‐25, respectively) as cathode materials have been prepared via a combined EDTA‐citrate complexing sol‐gel method. The effects of Cu contents on the crystal structure, chemical stability, electrical conductivity, thermal expansion coefficient (TEC) and electrochemical properties of BFC‐ x materials have been studied. All the BFC‐ x samples exhibit the cubic phase with a space group Pm3m (221). The electrical conductivity decreases with increasing Cu content. The maximum electrical conductivity is 60.9 ± 0.9 S cm −1 for BFC‐20 at 600 °C. Substitution of Fe by Cu increases the thermal expansion coefficient. The average TEC increases from 20.6 × 10 −6 K −1 for BFC‐10 to 23.7 × 10 −6 K −1 for BFC‐25 at the temperature range of 30–850 °C. Among the samples, BFC‐20 shows the best electrochemical performance. The area specific resistance (ASR) of BFC‐20 on SDC electrolyte is 0.014 Ω cm 2 at 800 °C. The single fuel cell with the configguration of BFC‐20/SDC/NiO‐SDC delivers the highest power density of 0.57 W cm −2 at 800 °C. The favorable electrochemical activities can be attributed to the cubic lattice structure and the high oxygen vacancy concentration caused by Cu doping.